Exploring the Green Development of Large Scale Sports Events in China from the Perspective of Ecological Civilization - Xiong, Dan (International Journal of Social Sciences and Public Administration, 2024)
China attaches great importance to the development and construction of ecological civilization, but the hosting of large-scale sports events often involves ecological environment problems caused by the construction of sports facilities during the preparation stage, urban traffic congestion caused by the rapid increase in population during the event hosting stage, and the waste of resources caused by the low utilization rate of sports facilities during the later stage of the event. The concept of harmonious coexistence between humans and nature serves as a theoretical guide for the green development of large-scale sports events in China. How to effectively reduce the negative impact of large-scale sports events on the ecological environment and achieve green development of large-scale sports events is an urgent problem that needs to be solved. Therefore, this study uses methods such as literature review and logical analysis to sort out and analyze the current development status of integrating green concepts into sports events. Based on this, relevant suggestions are proposed to achieve a harmonious and win-win situation between events and the environment.